Protein adsorption at a gold electrode studied by in situ scanning tunnelling microscopy - Davis, J; Halliwell, C; Hill, H; Canters, G; Amsterdam, v; Verbeet, M (1998)
The in situ adsorption, under physiological conditions, of azurin molecules at a gold electrode surface has been monitored at the molecular level by scanning tunnelling microscopy. The introduction of free cysteine residues into the surface of the redox protein by structurally conservative mutagenesis allows the immobilisation to be controlled in a manner in which the protein electrochemical activity is retained.